Biodiesel: A New Oildorado? - Manuel Frondel; Jörg Peters (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2005)
Guaranteeing tax reductions and exemptions, the European governments intend to increase the share of biofuels in total EU fuel consumption to 5.75% by 2010. The financial support of this EU objective is frequently justified by expected positive environmental impacts, most notably the mitigation of climate change, and by favorable employment effects in the agricultural sector. This paper investigates the environmental and economic implications of the support of rapeseed-based biodiesel as a substitute for fossil diesel.Based on a survey of recent empirical studies, we find that the energy and greenhouse gas balances of this environmental strategy are clearly positive.Yet, its overall environmental balance is currently far from being unequivocally positive. Most importantly, biodiesel is not a cost-efficient emission abatement strategy. Thus, for the abatement of greenhouse gases,we recommend more efficient alternatives based on both renewable and conventional technologies.
Keywords: Q42; Q28; Q58; 330; Renewable Energy; Environmental Policy; Greenhouse Gas Emissions; Klimaschutz; Förderung regenerativer Energien; Biokraftstoff; Nutzwertanalyse; EU-Staaten